Effects of L1 definitions and cognate status of test items on the Vocabulary Size Test. (April 2013) - Elgort, Irina
This study examines the development and evaluation of a bilingual Vocabulary Size Test (VST, Nation, 2006). A bilingual (English–Russian) test was developed and administered to 121 intermediate proficiency EFL learners (native speakers of Russian), alongside the original monolingual (English-only) version of the test. A comparison of the bilingual and monolingual test scores showed that participants achieved significantly higher scores on the bilingual version of the test. Accuracy of responses to individual test items was reliably higher when the meanings of test items were presented in the L1 (Russian) and when these items were cognates. The findings also revealed that the bilingual version is likely to be a more sensitive measure of written receptive vocabulary knowledge. Finally, analyses showed that the effect of using L1 for multiple-choice options is likely to be larger for low-proficiency learners and that the difference in response accuracy to cognates and non-cognates decreases as item frequency increases. The paper concludes with recommendations on developing and using bilingual vocabulary size tests.